Nonlinear Response of Fuel Price Returns to Monetary Policy : A Regime-Switching Approach - Ray, Koustubh Kanti; Das, Chandrabhanu (Indian Journal of Finance, 2024)
Purpose : The paper sought to understand the influence of call money rates and forward premiums as monetary policy stances on oil and natural gas prices in Indian markets. Methodology : The study employed the Markov-switching dynamic regression model as a regimeswitching methodology to investigate the nonlinear response of fuel price returns to monetary policy. The study considered monthly oil and natural gas prices from January 2005 to July 2019. The monthly call money rates and forward premia from January 2005 to July 2019 were extracted from the RBI database. The final data sample consisted of 175 monthly observations. The study used Stata statistical software for data analysis. Findings : The gasoline returns showed a noteworthy correlation between call money rates and forward premia. However, according to the model fitting tests, monetary policy variables only seemed to impact oil price returns during a crisis. In the same way, for natural gas, the present return was only affected by the lag return when things were calm. Additionally, fuel returns persist longer during a crisis, a sign of increased use and a dearth of substitutes for the good. Practical Implications : The study’s conclusions have policy ramifications for monetary policy instruments like forwarding premia and calling money that can be used to influence the price of oil. Government and regulatory agencies may consider substituting natural gas for fossil fuels in the entire fuel mix, making it more environment friendly. Originality : The study used real-time commodity (oil and natural gas) price data and policy measures (RBI call rate and forward premium) to adopt a model to examine policy intervention’s effect on commodity prices in the Indian context.